Application of scanning electron diffraction in the transmission electron microscope for the characterisation of dislocations in minerals. (30th July 2018) - Nzogang, Billy C.; Mussi, Alexandre; Cordier, Patrick
Abstract: We present an application of scanning electron diffraction for the characterisation of crystal defects in olivine, quartz and phase A (a high pressure hydrated phase). In this mode, which takes advantage of the ASTAR™ module from NanoMEGAS, a slightly convergent probe is scanned over the sample with a short acquisition time (a few tens of ms) and the spot patterns are acquired and stored for further post-processing. Originally, orientation maps were constructed from automatic indexing at each probe location. Here we present another application where images are reconstructed from the intensity of diffraction spots, producing either so-called 'virtual' bright- or dark-field images. We show that these images present all the characteristics of contrast (perfect crystal or defects) of conventional transmission electron microscopy images. Data are acquired with a very short time per probe location (a few tens of milliseconds), this technique appears very attractive for the characterisation of beam-sensitive materials. However, as the acquisition is done at a given orientation, fine tuning of the diffraction conditions at a given location for each reflection is not possible. This might present a difficulty for some precise, quantitative contrast analysis.